Mechanisms Underlying Mechanical Responses to Ephedra herb of Isolated Rabbit Urinary Bladder and Urethra, a Possible Stress Urinary Incontinence Therapeutic - Kazuhide Ayajiki; Toshio Kimura; Kohei Yamamizu; Tomio Okamura (Elsevier, 2008)
To compare the mechanisms underlying mechanical responses to ephedrine and Ephedra herb, a main component of Kakkon-to, in isolated male and female rabbit urinary bladder and urethral strips, responses of isolated strips to the agents were recorded in organ bath systems. Ephedrine and Ephedra herb relaxed the female urinary bladder to the similar extent. These relaxations are reversed to contractions by timolol. In the presence of timolol, ephedrine produced less contraction of urethral strips in the female than those in the male; this contraction was abolished by prazosin. Ephedra herb contracted the female urethra less than that of the male, and the contraction was stronger than that by ephedrine. The contraction caused by Ephedra herb in strips treated with timolol was significantly inhibited by prazosin. The prazosin-resistant contraction of the female urethra was greater than that of the male. Quinacrine, a phospholipase A2 inhibitor, indomethacin, and AA861, a 5-lipoxygenase inhibitor, inhibited the contraction. The contraction was inhibited by ZK 158252, a leukotriene (LT) B4-receptor antagonist. These findings suggest that Ephedra herb contracts the urethra via arachidonic acid metabolites together with α1-adrenoceptor stimulation. The metabolites produced by 5-lipoxygenase may stimulate LTB4, but not CysLt1, receptors. These contractile components induced by Ephedra herb and Kakkon-to might be effective for the treatment of stress urinary incontinence. Keywords:: stress urinary incontinence, Ephedra herb, ephedrine, urethral contraction, arachidonic acid metabolite